A STUDY ON THE ABILITY OF THE SECOND YEAR STUDENTS OF SMP MUHAJIRIN SEI GALUH IN WRITING RECOUNT TEXT - Eha Anggreta; Fadly Azhar; Rumiri Aruan (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The Purpose of this study is to find out the ability of the second year students of SMP Muhajirin Sei Galuh un writing recount text. In this research, the data was obtained from students’ writing scores. The test is in this form of a paragraph because the test required the respondents to write a paragraph in the form of written recount text. There are five components of writing: grammar, organization, vocabulary, content, and mechanic (Jacob:1981). The writer analyzed the ability of the second year students based on five category: Excellent, good, mediocre, poor and very poor. The participants in this study are 30 students from VIII A of SMP Muhajirin Sei Galuh. The result of this study described that a number of students faced a problem in grammar.Content is the highet average score. Based on these findings, it can be concluded that the ability of the second year students of SMP Muhajirin Sei Galuh is in Mediocre level. Although the students still faced some difficulties in writing recount test.Key words: Writing ability, recount text